Optimisation of Heart Failure Management in Nursing Homes Using Point-of-Care Ultrasonography: Harmonious Trial Rationale and Design - Homar Vesna; Švab Igor; Lainščak Mitja (Sciendo, 2020)
Heart failure is common in the nursing home population and presents many diagnostic and therapeutic challenges. Point-of-care ultrasonography is a bedside method that can be used to assess volume status more reliably than clinical examination. This trial was conceived to test whether point-of-care ultrasonography-guided management improves heart failure outcomes among nursing home residents.